Predictors of stroke-associated pneumonia after the first episode of acute ischaemic stroke - Ahmad Tajudin, Noradina; Ahmad, M. A.; Uduman, A.; Basri, Hamidon (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Objectives: Pneumonia is one of the most common complications of stroke with significant impact on patients' outcome. The aim of this study is to look for the predictors of stroke-associated pneumonia (SAP) and its 30-day mortality and to analyse the survival of ischaemic stroke patients with pneumonia. Methodology: This is a prospective observational study, involving all acute first time ischaemic stroke patients admitted to a tertiary hospital that fulfilled the inclusion and exclusion criteria over a 6-month period. Demographic data were obtained on admission. Patients were reassessed for SAP, on day 5 and day 30. Assessment was done using the National Institutes of Health Stroke Scale (NIHSS) score, Barthel index and modified Rankin scale (MRS). All patients with pneumonia were assessed with the pneumonia severity index (PSI) for SAP. Results: One hundred and twenty patients were enrolled consecutively within the 6-month study period. 15.8% developed SAP. Independent predictors of SAP were clinical dysphagia (OR 76.32; 95%CI 4.46 to 1307.05), random blood glucose (RBS) on admission (OR 1.34; 95%CI 1.06 to 1.68) and NIHSS score on admission (OR 1.15; 95%CI 1.02 to 1.30). Independent predictors for 30-day mortality were NIHSS score on day 5 (OR 1.20; 95%CI 1.08 to 1.33) and occurrence of pneumonia (OR 14.90; 95% CI 3.34 to 66.42). There was a significant difference in mean survival between SAP and non-SAP patients. Conclusions: Clinical dysphagia, RBS on admission and NIHSS score on admission were independent predictors of SAP. NIHSS score on day 5 and pneumonia were independent predictors of 30-day mortality. SAP patients had shorter survival time compared to non-SAP patients.